Two FSHR variants, haplotypes and meta-analysis in Chinese women with premature ovarian failure and polycystic ovary syndrome - Du, Jing; Zhang, Wenjing; Guo, Lingli; Zhang, Zhaofeng; Shi, Huijuan; Wang, Jian; Zhang, Huiqin; Gao, Linghan; Feng, Guoyin; He, Lin (Molecular genetics and metabolism, 2010)
In this study, two polymorphisms of follicle stimulating hormone receptor ( FSHR) gene were analysed in the case-control sample using 40 premature ovarian failure (POF) patients, 60 polycystic ovary syndrome (PCOS) patients and 92 healthy controls. All subjects were unrelated Han Chinese from Shanghai. No difference was observed on the allelic or genotypic distribution of FSHR gene polymorphisms between the groups. However, the two-marker haplotypes covering components Thr307Ala (rs6165) G and Asn680Ser (rs6166) A were observed to be significantly associated with PCOS ( p = 0.007, corrected p = 0.042). Meanwhile, a meta-analysis including our study (altogether six POF and eight PCOS studies) showed significant association between rs6166 marker and PCOS ( p < 0.05). The results suggest that FSH receptor might play a role in genetic susceptibility to PCOS. However, confirmatory studies in independent samples are needed.